(untitled) (Journal of Universal Science Research, 2023)
English is the official language of more than 60 countries in the world. English that grew out of the West Germanic language family spread around the world with the expansion of the British Empire. Slowly, English became the leading language of international, trade, education, and official communication. It has widely dispersed across the globe due to globalization. Its dissemination and importance accelerated with growing interconnectedness for trade and commerce. English has become the reason for economic growth of countries around the world. This paper discusses the integral role played by English language in escalating the country’s economy